Possibility of laboratory assessment of the state of connective tissue - G. A. Berezovskaya; V. L. Emanuel (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
This article deals with the possibilities of laboratory assessment of the state of the connective tissue. It contains brief information about its structure, functions and roles of the various components in the development of pathological processes, and provides laboratory diagnostic methods of these changes.